2023
DOI: 10.32479/ijeep.14059
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Energy Management Disclosure : Empirical Evidence from Indonesia Stock Exchange

Abstract: Energy is one of the vital needs for humans. Indonesia as a developing country faces problems in ensuring the availability of energy. The aim of this research is to explore the development of practice energy management disclosure in accordance with GRI 302 (energy) in energy sub-sector companies listed on the Indonesia Stock Exchange (IDX) through disclosures issued by each company. This study uses secondary data collected from reports published by energy sub-sector companies listed on the Indonesia Stock Exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…That is, does it reflect reliability? Meanwhile, failure in the auditor's skill offsets the auditor's inability to detect in the course of the incidental snowfall that is occurring in the event of an error (Meiryani, Huang, Lindawati, et al, 2023). They confirmed that although the user's knowledge base did not have access to the evidence collected during the audit process, they only assessed the actual quality of the audit process directly if they relied on the reputation of the auditor's inability to provide an opinion.…”
mentioning
confidence: 94%
“…That is, does it reflect reliability? Meanwhile, failure in the auditor's skill offsets the auditor's inability to detect in the course of the incidental snowfall that is occurring in the event of an error (Meiryani, Huang, Lindawati, et al, 2023). They confirmed that although the user's knowledge base did not have access to the evidence collected during the audit process, they only assessed the actual quality of the audit process directly if they relied on the reputation of the auditor's inability to provide an opinion.…”
mentioning
confidence: 94%
“…Indonesian waters, with their expansive area, harbor a diverse array of biological resources (that can enhance the local community's economic income) (Hasan and Widodo 2021;Indarjo et al 2022;Hasan et al 2022;Meiryani et al 2023;Serdiati et al 2023), both domestically and internationally (Gani et al 2021;Ndobe et al 2023;Indarjo et al 2022;Hasan et al 2023;Nurjirana et al 2023). This condition also applies to the waters of Tarakan Island (Indarjo et al 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…Chacunda gizzard shad (Anodontostoma chacunda, Hamilton, 1822) is distributed in Indo-West Pacific Waters (Froese and Pauly 2021), such as The Bay of Bengal, Bangladesh (Hanif et al 2019), The Cua Tieu River, Mekong Delta, Vietnam (Dong et al 2022), Coastal Area in Duyen Hai District, Tra Vinh Province, Vietnam (Dong and Tu 2021), Shatt Al-Arab River, Southern Iraq (Taher et al 2019), Bali (Agustiana et al 2023), South of Bangka Waters (Aisyah et al 2022), Lamongan Waters (Anam et al 2023), and also Tarakan waters, North Kalimantan (Jabarsyah et al 2021). Anodontostoma chacunda has a significant economic value (Meiryani et al 2023), with a price range of about USD 0.64-0.96/kg. According to Agustiana et al (2023), the protein concentration from A. chacunda has the best base material of ash and carbohydrate content.…”
Section: Introductionmentioning
confidence: 99%